Zooplankton in lakes and fiords along the northern coastline of Ellesmere Island (Ward Hunt Island observatory) - Vincent, Warwick; Hove, Patrick Van; Veillette, Julie; Létourneau, Louis (Canadian Cryospheric Information Network, 2011)
Zooplankton was sampled from Lake A on 8 June 1999 and Disraeli Fiord on 9 June 1999. At Lake A, a hole was cut through the ice and was kept open for 3 days before zooplankton sampling. A 1-m-long conical plankton net mesh size 100 μm; mouth diameter 20 cm) was used to sample the zooplankton. Duplicate net tows were made sequentially at the following depths: 2.5, 5, 7.5, 10, 12.5, 15, 17.5, 20, 25, and 30 m. The net was towed by hand vertically at approximately 1 m/s from a given depth to the surface. In Disraeli Fiord, logistical constraints allowed us only a single tow from the brackish-water layer, from 30 m to the surface. All samples were preserved with final concentrations of 0.2% glutaraldehyde and 0.02% formaldehyde, a preservative used for phytoplankton studies but which gave very good preservation of zooplankton. The specimens were identified and enumerated using a binocular microscope (X32 magnification). At Milne Fiord, two zooplankton vertical tows (14-0 m then 50-0 m, through the same hole) were made on 4 July 2009 with a 39-cm-long net with a 210-um mesh size and diameter of 13 cm. The zooplankton samples were preserved with formaldehyde (final concentration 10%), and all individuals were then counted and identified to species level using a binocular microscope. : Purpose: The analysis of zooplankton species compositon within the water column was made in order to characterize the biological environment of lakes and fiords. : Summary: Not Applicable